Basic Newborn Life Support (BNLS) for members of the general public in natural disaster and conflict areas: A PHAID (PreHospital Aid) initiative - Abdul Qader Tahir Ismail (International Journal of First Aid Education)
Aim The PHAID (PreHospital Aid) initiative aims to reduce morbidity and mortality in regions affected by natural disasters or conflict by providing basic equipment and preemptive training to members of the public. The newborn arm involved creating a basic newborn life support (BNLS) algorithm. Size of Problem / Opportunity Low- and middle-income countries (LMIC) are at greater risk of natural disasters and military conflict, which adversely impact already strained healthcare systems. Worldwide, ~60 million births occur outside healthcare facilities, mostly in LMIC. At birth, ~10% of babies do not breathe and require intervention, without which, hypoxic ischemic encephalopathy (brain injury due to starvation of blood and/or oxygen) and multiorgan damage can occur. Annually, there are >1 million cases of neonatal encephalopathy, of which 96% are in LMIC. Results We produced an expert-informed, simplified algorithm, feasible to be carried out by members of the public, focusing on drying and keeping warm, delayed cord clamping, recognizing which babies need help, and effectively delivering inflation breaths. Conclusion In areas affected by conflict or natural disasters, newborn babies that do not breathe will die or suffer hypoxic ischemic brain injury. In that setting, there is benefit in providing members of the public with information and training to carry out a basic form of newborn life support. This is reflected in the PHAID newborn algorithm.